Adsorption of Protein on H-Beta Zeolite - Ismail, Noor Maizura (2005)
The adsorption of two proteins, cytochrome c and Î±-chymotrypsin onto H-Beta zeolite was studied. The effectof pH on the adsorption capacity was studied at three different pHs, namely 3, 6, and 9. The adsorption capacity for cytochrome c and Î±-chymotrypsin was found to be the highest at pH 9 and pH 6 respectively. Increase in pH higher than their pI lead to the decrease in the adsorption capacity for both proteins. This is postulated to be due to electrostatic repulsion between protein and the surface of adsorbent. The adsorption characteristics of different proteins onto H-Beta zeolite depend, apart of experimental conditions used, on protein physical and chemical properties. The adsorption isotherm data of protein is well fitted to the Langmuir model. FTIR analysis was performed for both H-Beta zeolite with and without adsorbed protein to study the interaction between the protein and H-Beta zeolite surface. The observed decrease in the intensities of amide groups in protein structure is most likely a consequence of binding of protein onto HBeta zeolite.